Impact of Aircraft Noise on Communities Near Belgrade Airport - Emir Ganić; Jurica Ivošević; Bojana Mirković (Promet (Zagreb), 2021)
The aim of this research was to examine the impact of aircraft noise on communities near the Belgrade Airport by conducting short-term noise measurements. Apart from the noise abatement procedure published in the Aeronautical Information Publication for Belgrade Airport, there are still neither publicly available reports of the actual efforts made towards the aircraft noise reduction nor the description of the current noise situation. In order to estimate the current noise situation, eighteen aircraft overflight noise measurements were taken in two settlements in specific sound-sensitive community areas around the Belgrade Airport. The results showed that level differences between background noise and aircraft overflights were higher than 10 dB for each measurement and could be considered significant. Furthermore, preliminary compatibility analysis with acoustic zoning was performed. Average daily noise levels were estimated from these short-term measurements and were compared to legal noise limits for different acoustic zones. The results indicate that in some cases noise levels exceed the legal threshold, which should encourage land use planners to include the issue of Belgrade acoustic zoning on the agenda, but also prompt Belgrade Airport to implement continuous noise and flight tracks monitoring.